Border Cultures / Cultures at the Border: Гранични култури / култури на границата - Šeleva, Elizabeta; Kirkova, Anastazija (Identities: Journal for Politics, Gender and Culture, 2003)
Author(s): Elizabeta Šeleva | Елизабета Шелева Title (English): Border Cultures / Cultures at the Border Title (Macedonian): Гранични култури / култури на границата Translated by (Macedonian to English): Anastazija Kirkova | Анастазија Киркова Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 1 (Summer 2003) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 123-139 Page Count: 16 Citation (English): Elizabeta Šeleva, “Border Cultures / Cultures at the Border,” translated from the Macedonian by Anastazija Kirkova, Identities: Journal for Politics, Gender and Culture, Vol. 2, No. 1 (Summer 2003): 123-139. Citation (Macedonian): Елизабета Шелева, „Гранични култури / култури на границата“, Идентитети: списание за политика, род и култура, т. 2, бр. 1 (лето 2003): 123-139.